2017
DOI: 10.1371/journal.pone.0179075
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic variation and diversity in clinical Streptococcus pneumoniae isolates from invasive and non-invasive sites

Abstract: Streptococcus pneumoniae is responsible for a variety of invasive and non-invasive human infections. There are over 90 serotypes of S. pneumoniae differing in their ability to adapt to the different niches within the host. Two-dimensional gel electrophoresis was used to discriminate clinical S. pneumoniae isolates recovered from either blood cultures (invasive site isolates) or other sites, including sputum, tracheal aspirate, ear, eye and skin swabs (non-invasive site isolates). Global protein expression prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…The importance of transition metals in the physiology of S. pneumoniae, as shown previously, was confirmed by our whole cell proteomics data [13,16]. In accordance with the literature, the PCA analysis in this study showed that different strains, with differences in serotype and genetic background, have unique proteomic profiles [51]. Nevertheless, the two serotypes examined in the current study responded similarly to differences in metal availability.…”
Section: Discussionsupporting
confidence: 91%
“…The importance of transition metals in the physiology of S. pneumoniae, as shown previously, was confirmed by our whole cell proteomics data [13,16]. In accordance with the literature, the PCA analysis in this study showed that different strains, with differences in serotype and genetic background, have unique proteomic profiles [51]. Nevertheless, the two serotypes examined in the current study responded similarly to differences in metal availability.…”
Section: Discussionsupporting
confidence: 91%
“…In combination with a transcriptional analysis, this could reveal potential post-transcriptional regulatory mechanism important for host-niche adaptation, not discovered by a transcriptional analysis alone. Currently, a limited number of studies have investigated the proteome of pneumococci in response to invasive niches conditions ( Bae et al, 2006 ; Bittaye et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial cells were pelleted from the culture media by centrifugation at 2500 × g for 10 min and washed with sterile water, to lyse blood cells, then with sterile PBS. Preparation of protein extracts and analysis by 2D gel electrophoresis was undertaken within the University of Aberdeen Proteomics facility following protocols described previously 17 .…”
Section: Methodsmentioning
confidence: 99%